KEDISIPLINAN GURU DALAM MENGAJAR TERHADAP MINAT BELAJAR MATA PELAJARAN IPS - Norhyatun Norhyatun; Novianti Rahmawati; Nuriana Astra Ningsih (STKIP MUHAMMADIYAH SAMPIT, 2018)
From interviews with one of the students obtained the fact that student will be less interst in following the lesson if the teacher lat to class and they would like a lesson if the teacher how to teach it interesting and fun. Vice versa if the does not like a lesson, it is because she does not like the way teachers teach. If she did not like one of the teachers who teach in the classroom, she is usually less attention and understand what is convenyed by the teacher. [Mely, interviews20 April 2015]. The purpose of this research is to know something no influence perceptions of student discipline teachers teaching against IPS interest in learning subjects in class VIII at SMP Negeri 9 Sampit in academic year 2015/2016. The type of research used in this research is quantitative research. The type of approach used is a correlation study.Based on the survey result revealed that the values of R square (R2) to the percentage contribution of the variable students perceptions about the discipline of teachers in teaching the learning interest of 16,7% and the remaining 83% is influence by other factors such individual factors, and social factors.